2008
DOI: 10.1063/1.2834705
|View full text |Cite
|
Sign up to set email alerts
|

Structural, optical, and magnetic characterization of monodisperse Fe-doped ZnO nanocrystals

Abstract: The results on the synthesis and characterization of highly monodisperse Fe-doped ZnO nanocrystals are presented. Stable suspensions of these materials were produced in an ethanol solution at room temperature. To promote crystal growth, the suspensions of nanocrystals were aged in contact with their mother liquors. X-ray diffraction characterization of doped systems at various Fe-atomic fractions x confirmed the exclusive formation of the host ZnO with the wurtzite structure. High resolution transmission elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(30 citation statements)
references
References 22 publications
4
23
0
Order By: Relevance
“…To obtained the optical gap the linear part of F(R) 2 curve was extrapolated until it intersects the energy axis. The optical gap of ZnO dried at 100˚C determined by the above method to be 3.52 eV, which is higher than that for bulk ZnO (3.4 eV) [29]. The corresponding optical gaps are seen to be shifted to lower energies with increasing dry temperature.…”
Section: Resultsmentioning
confidence: 83%
“…To obtained the optical gap the linear part of F(R) 2 curve was extrapolated until it intersects the energy axis. The optical gap of ZnO dried at 100˚C determined by the above method to be 3.52 eV, which is higher than that for bulk ZnO (3.4 eV) [29]. The corresponding optical gaps are seen to be shifted to lower energies with increasing dry temperature.…”
Section: Resultsmentioning
confidence: 83%
“…An increase of 18 meV in optical band gap of Fe doped films prepared by sol-gel spin coating method was reported by Xu et al [13]. Parra-Polomino et al [14] also reported an increase, of 340 meV, in optical band gap of iron doped nanocrystals prepared by chemical route. n-type semiconducting metal oxides can also be used for gas sensing as they were able to exhibit variation in some electrical parameters, viz.…”
Section: Introductionmentioning
confidence: 71%
“…Previously, Srivastava et al [1] reported an increment in optical band gap in Fe doped ZnO films of a thickness 500 nm obtained by sol-gel spin coating using precursor solutions of the molarity of 0.1 M. It was concluded that sp hybridization is responsible for this behavior. Other reports in the literature regarding the increase in the band gap of Fe doped ZnO with an increase in dopant concentration, explained it by Burstein Moss effect [13] and quantum confinement [14].…”
Section: Uv-vis Spectra and Optical Band Gapmentioning
confidence: 99%
“…The similar results are also reported by others. For example, Parra-Palomino et al [25] reported that the optical band-gap gradually increased with the increasing Fe-doping concentration in ZnO nanocrystals. However, Chen et al [17] and Wang et al [20] found that the optical band-gap of ZnO thin film gradually decreased with the increasing Fe-doping concentration.…”
Section: Resultsmentioning
confidence: 98%